Preoperative vitamin D level as a post-total thyroidectomy hypocalcemia predictor: a prospective study - Soares,Carlos Segundo Paiva (2021)
Abstract Introduction: Hypocalcemia is one of the most common complications after total thyroidectomy. Preoperative serum vitamin D concentration has been postulated as a risk factor for this complication. However, the subject is still controversial and the role of vitamin D in the occurrence of hypocalcemia remains uncertain. Objective: To evaluate the capability of preoperative vitamin D concentrations in predicting post-total thyroidectomy hypocalcemia. Methods: Forty-seven total thyroidectomy patients were prospectively evaluated for serum 25(OH) vitamin D, calcium and parathyroid hormone before surgery, Calcium every 6 hours, and parathyroid hormone 8 hours post-operatively. Patients were divided according to postoperative corrected calcium into groups without (corrected calcium ≥8.5 mg/dL) and with hypocalcemia (corrected calcium <8.5 mg/dL), who were then evaluated for preoperative 25(OH) vitamin D values. Results: A total of 72.3% of cases presented altered 25(OH) vitamin D preoperative serum concentrations and 51% evolved with postoperative hypocalcemia. The with and without hypocalcemia groups did not differ for preoperative 25(OH) vitamin D (p = 0.62). Univariate analysis showed that age (p = 0.03), postoperative PTH concentration (p = 0.02), and anatomopathological diagnosis of malignancy (p = 0.002) were predictors of postoperative hypocalcemia. In multivariate analysis only parathyroid hormone in postoperative (p = 0.02) was associated with post-total thyroidectomy hypocalcemia. Conclusion: Preoperative serum concentrations of 25(OH) vitamin D were not predictors for post-total thyroidectomy hypocalcemia, whereas postoperative parathyroid hormone influenced the occurrence of this complication.